Clinical phenotypes and outcomes of pulmonary hypertension due to left heart disease: Role of the pre-capillary component. - Sergio Caravita; Andrea Faini; Sandy Carolino D'Araujo; Céline Dewachter; Laura Chomette; Antoine Bondue; Robert Naeije; Gianfranco Parati; Jean-Luc Vachiéry (PLoS ONE)
Background In pulmonary hypertension (PH), both wedge pressure elevation (PAWP) and a precapillary component may affect right ventricular (RV) afterload. These changes may contribute to RV failure and prognosis. We aimed at describing the different haemodynamic phenotypes of patients with PH due to left heart disease (LHD) and at characterizing the impact of pulmonary haemodynamics on RV function and outcome PH-LHD. Methods Patients with PH-LHD were compared with treatment-naïve idiopathic/heritable pulmonary arterial hypertension (PAH, n = 35). PH-LHD patients were subdivided in Isolated post-capillary PH (IpcPH: diastolic pressure gradient, DPG<7 mmHg and pulmonary vascular resistance, PVR≤3 WU, n = 37), Combined post- and pre-capillary PH (CpcPH: DPG≥7 mmHg and PVR>3 WU, n = 27), and "intermediate" PH-LHD (either DPG <7 mmHg or PVR ≤3 WU, n = 29). Results Despite similar PAWP and cardiac index, haemodynamic severity and prevalence of RV dysfunction increased from IpcPH, to "intermediate" and CpcPH. PVR and DPG (but not compliance, Ca) were linearly correlated with RV dysfunction. CpcPH had worse prognosis (p<0.05) than IpcPH and PAH, but similar to "intermediate" patients. Only NTproBNP and Ca independently predicted survival in PH-LHD. Conclusions In PH-LHD, haemodynamic characterization according to DPG and PVR provides important information on disease severity, predisposition to RV failure and prognosis. Patients presenting the CpcPH phenotype appear to have haemodynamic profile closer to PAH but with worse prognosis. In PH-LHD, Ca and NTproBNP were independent predictors of survival.